Gelatinous polyethylene in the treatment of the anophthalmic cavity - Schellini, Silvana Artioli [UNESP]; Xavier, Adriana P. [UNESP]; Hoyama, Érika [UNESP]; Rossa, Romualdo [UNESP]; Pellizon, Cláudia [UNESP]; Marques, Mariângela Esther Alencar [UNESP]; Padovani, Carlos Roberto [UNESP] (Swets & Zeitlinger Publishers, 2002)
PURPOSE: Gelatinous polyethylene (GP) has been used as an orbital implant to evaluate volume maintenance and tissue reaction in the anophthalmic socket in a rabbit model. METHODS: Twenty-eight Norfolk white rabbits underwent unilateral evisceration with placement of 2ml GP (GP group - 16 animals) or 2ml 0.9% sodium chloride solution (Control group - 12 animals). Animal behavior, postoperative tissue response and socket conditions were evaluated. The animals were sacrificed at 7, 15, 30 and 60 days after the surgery and the bulbs were enucleated; volume maintenance and histopathological evaluation were done in the enucleated bulbs. The results were submitted to statistical analysis. RESULTS: All animals showed normal behavior. The orbital volume maintenance was better in the GP group. Histopathology in the GP animals showed mild tissue inflammation throughout the evaluation period and a thin pseudocapsule formation surrounding the orbital implant material. CONCLUSION: The clinical findings, good orbital volume maintenance and mild inflammatory tissue response make GP a good choice to replace the lack of volume in anophthalmic socket reconstruction.
Keywords: Anophthalmic socket; Gelatinous polyethylene; Histopathology; Orbital volume; Rabbits; Socket reconstruction; polyethylene; sodium chloride; animal experiment; animal tissue; anophthalmia; controlled study; enucleation; evisceration; gel; histopathology; implant; inflammation; nonhuman; rabbit; statistical analysis; Animal; Biocompatible Materials; Comparative Study; Eye Enucleation; Gelatin; Models, Animal; Orbit; Orbital Implants; Polyethylenes; Prosthesis Implantation; Random Allocation; Treatment Outcome